25-Hydroxyvitamin D Deficiency: Impacting Deep-Wound Infection and Poor Healing Outcomes in Patients With Diabetes. (July 2019) - Smart, Hiske; AlGhareeb, Ahmed Mohamed; Smart, Sally-Anne
ABSTRACT: BACKGROUND: The Kingdom of Bahrain has a high incidence of diabetes and associated foot complications. Simultaneously, low 25-hydroxyvitamin D (25[OH]D) levels are common in this population and may be associated with the traditional clothing used in desert climates. METHODS: This investigation compared 25(OH)D levels and glycemic control with quantifiable wound healing parameters in a prospective, analytic, nonexperimental, cross-sectional pilot study. Consecutive consenting adult patients (N = 80) who presented to the regional wound care unit in January 2016 with either an existing or new wound were included. Collected data included three-dimensional wound photography, NERDS and STONEES criteria, and an X-ray with a positive probe-to-bone test. Blood values for 25(OH)D and hemoglobin A1c (HbA1c ) were collected simultaneously. RESULTS: Diabetes mellitus (types 1 and 2) was present in 90% of the sample patients. No patient had sufficient 25(OH)D levels; 15% had insufficient levels (30–50 ng/mL), and deficiency (levels <#20 ng/mL) was found in 85% of the sample. Males were slightly less affected by 25(OH)D deficiency compared with females (82.4% vs 91.3%). Poor glycemic control (HbA1c levels >#6.8%) was found in 69.4% (n = 50) of the persons with diabetes included in the sample. Those with both diabetes mellitus and a 25(OH)D deficiency (76.3%; n = 61) were more likely to demonstrate healing difficulty (40.9%; n = 25) or present with a stalled or deteriorating wound (44.2%, n = 27). A 3° F or higher periwound surface temperature elevation over a mirror image site was present in 82.5% of all wounds. Exposed bone in the ulcer base was found in 50% of the cases. For persons with diabetes, general linear modeling statistical analysis (adjusted R 2 value = 47.9%) linked poor wound healing with three studied variables: 25(OH)D deficiency, poor glycemic control, and an exposed bone in the wound bed. CONCLUSIONS: Vitamin D may be an overlooked factor in the pathophysiology of diabetic foot ulcer development and subsequent delay in wound healing outcomes. The authors recommend adding 25(OH)D deficiency to the list of multifactorial aggravating factors providers should consider correcting in this subgroup of patients.